Perfil metabólico e avaliação radiográfica de potros Mangalarga Marchador recebendo gramínea com baixa relação Ca:oxalato e sal mineralizado corrigido com diferentes relações de Ca:P - Debora Roque de Freitas Andrade (2022)
Foals fed calcium-deficient diets in the first year of life may have structural weaknesses and metabolic disorders that, consequently, detract from their economic value and future athletic performance. Pennisetum purpureum (elephant grass) is a forage adapted to the edaphoclimatic conditions in Brazil, used to feed equines mainly during the dry season. This grass has high concentrations of oxalate, which can form an insoluble compound with dietary calcium (Ca), reducing its absorption, predisposing animals to secondary nutritional hyperparathyroidism. This study aimed to verify whether the consumption of elephant grass as the only forage source, mineral salt ad libitum and supplementary concentrate with different ratios between Ca and P affects the metabolism of these minerals in weaned foals. Sixteen male foals, Mangalarga Marchador, aged between 5 and 10 months, were randomly divided into 4 groups differentiated by the Ca:P ratio of the supplementary concentrate that was supplied daily (2:1; 3:1; 5:1; 6:1) . Four blood samples were collected to evaluate Ca, P, magnesium (Mg), parathyroid hormone (PTH), gamma-glutamyltransferase (GGT), alkaline phosphatase (FA) and metabolomic analysis. Metabolomic analysis was performed to verify the metabolic profile in the serum of the animals, which resulted in 22 metabolites. Radiographic images were also taken to verify the occurrence of angular deformity and the cortical index. Collections were made at 0, 15, 43 and 71 days after the provision of experimental diets. There was a reduction (p<0.05) in serum Ca over time in all treatments, as well as an increase in PTH concentration. In addition, P was higher at 43 days after supply, being higher than the reference values. Comparing the intensity of the spectra, increases were observed in the metabolites 3-hydroxybutyrate, acetone, valine, isoleucine, leucine, creatine, phosphocreatine, creatinine, dimethyl sulfone, glucose, pyruvate, glycerol, N-acetylglucosamine, propionate, lactate, acetate, glycolate and taurine. Of the metabolites that showed a reduction in the intensity of the spectra are alanine, threonine and methionine. The 1H NMR analysis demonstrated high reproducibility between samples. The identification of the 22 metabolites in the serum of foals receiving oxalate-rich grass as the only forage source adds to the knowledge already established for the HNS, helping to better understand the scenario present in this disease.